A comparative examination of acute toxicities of three disazo dyes to freshwater macroinvertebrates Gammarus roeseli (Crustacea: Amphipoda) and Chironomus riparius (Insecta: Diptera). Issue 8 (14th September 2021) - Sari, Adile; Sari, Fikret
ABSTRACT: This study was conducted to assess the acute toxicity of three previously synthesised 5-(3′-amino-4′-arylazo-1H-pyrazole-5′-ylazo) barbituric acid dyes (dyes 1–3 ) using Gammarus roeseli (Crustacea: Amphipoda) and Chironomus riparius (Insecta: Diptera) and to compare their sensitivities to these dyes. The toxicity of the tested dyes was found to increase with lengthened exposure period in both bioassays. The azo dye toxicity to both species was determined to increase due to the presence of the nitro and chloro groups in the structure. G. roeseli exhibited more tolerance to the nitro group containing azo dye (dye 2 ) than C. riparius, whereas C. riparius exhibited more tolerance to the chloro group containing azo dye (dye 3 ) than G. roeseli ; however, the sensitivity of two species to the azo dye without these groups (dye 1 ) did not significantly differ. The results suggest that the sensitivity varies depending on the species and the azo dye structure and that both species are suitable for ecotoxicological tests of the azo dyes. Nevertheless, further studies are recommended to determine all aspects of the toxicity mechanisms of these azo dyes, to investigate their degradation products and to assess their actual risk in the environment based on the results of this study. GRAPHICAL ABSTRACT: UF0001